2021
DOI: 10.3390/f13010024
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Restoration Material for Abies koreana Based on Its Genetic Diversity on Mt. Hallasan

Abstract: The restoration of damaged or disrupted forests with genetically appropriate restoration planting material that can adapt to future environmental conditions will ensure the conservation of forest genetic resources. Abies koreana is endemic to the Republic of Korea, with declining populations under current environmental changes. In this study, we examined the genetic diversity of its largest population growing on Mt. Hallasan to determine the sampling size of planting material from the population that will ensu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 28 publications
0
10
1
Order By: Relevance
“…Within the representative subpopulation of Mt. Jirisan, 5 to 30 sample sizes were randomly extracted using Python (Chae et al 2022). We calculated the number of alleles in each sample size and compared them with the number of alleles on Mt.…”
Section: Sample Selection Strategiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Within the representative subpopulation of Mt. Jirisan, 5 to 30 sample sizes were randomly extracted using Python (Chae et al 2022). We calculated the number of alleles in each sample size and compared them with the number of alleles on Mt.…”
Section: Sample Selection Strategiesmentioning
confidence: 99%
“…Hallasan, an appropriate strategy representing the genetic characteristics of A. koreana on Mt. Hallasan was proposed; more than 35 individuals were suggested to be collected at a distance of 5 m to 10 m each (Chae et al 2022). Mt.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…shikokiana contained almost all of the genetic variability observed in adult tree populations [12]. Chae et al (2022) reported that sampling 35 individuals at 10 m intervals was the most effective in a study on selecting restoration materials for Abies koreana considering genetic diversity [13]. However, measures to protect genetic diversity are still lacking [14].…”
Section: Introductionmentioning
confidence: 99%